PENGARUH MEDIA WORDWALL TERHADAP PENGUASAAN KOSAKATA BAHASA INDONESIA PADA SISWA KELAS RENDAH: Literarur Review - Milza Mulyani Purtri; Alya Loviza; M.Habibi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Vocabulary mastery is a fundamental aspect of Indonesian language learning, es- pecially for lower elementary school students. However, many students still face challenges in mastering vocabulary optimally, partly due to monotonous and less varied teaching methods. This study aims to examine the effect of Wordwall media on Indonesian vocabulary mastery among lower elementary school students. This research employs a quantitative approach using the Systematic Literature Review (SLR) method, which involves four stages: database identification, title-based screening, abstract and keyword content matching, and final article selection. A total of 15 relevant articles were selected from databases including Google Scholar, Se- mantic Scholar, DOAJ, and Garuda, published between 2017 and 2026. The results of the literature review indicate that the use of Wordwall media has a positive effect on Indonesian vocabulary mastery in lower elementary school students. Wordwall is proven to create more interactive, engaging, and enjoyable learning environ- ments, which increase student motivation and active participation. Game-based learning activities help students understand and retain new vocabulary more effec- tively. Furthermore, Wordwall also has a positive impact on student learning out- comes and engagement. Therefore, Wordwall can be recommended as an innova- tive and effective alternative media for Indonesian language learning in elementary schools.